Muslim Indians Challenges, Struggles, and Contestations - Amit Pandya (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The most difficult challenge for Indian Muslim societies is their compilation to confront their Muslim identity in the socio-political arena. Although there are many Muslim scientists there who claim that Muslims are part of India and India is their homeland. However India is part of Darul Safe (Muslim-friendly) where jihad is meaningless. It also opposes referring to Hindus as kafir (unbelievers), with its negative and exclusionary connotations. However, the struggle of Muslims in India is still long, both social-political, educational and Indian government policies towards Muslims who are still discriminatory. Although, what is felt by Muslims there, also felt by Christians in the arena of contestation with Hinduism there.